Critical Care Nurses’ Experiences of Coping with Moral Distress - Forozeiya, Dana (Université d'Ottawa / University of Ottawa, 2017)
Over the last three decades, there has been a growing body of literature that has described moral distress as a prominent issue that negatively affects critical care nurses. However, little focus has been given to how nurses cope and continue on in their practice despite the hardship that moral distress can cause. This study sought to reveal nurses’ strategies of coping with moral distress to allow for a better understanding of this aspect of critical care nurses’ experiences. This study adopted a qualitative design that used Thorne’s (2008) approach to interpretative description. Face-to-face, semi-structured interviews were conducted with seven critical care nurses employed within two ICUs of a tertiary care academic hospital. Interviews were analyzed using Aronson’s (1995) approach to thematic analysis. The experience of coping with moral distress had an overarching theme of being “like grass in the wind.” Four major themes were identified: Going Against What I Think is Best, Moral Distress- It’s Just Inherent in Our Job, It Just Felt Awful, and Dealing with It.
Keywords: moral distress; coping; critical care; intensive care; nursing